Characteristics of Malignant Eyelid Basal Cell Carcinoma in Cicendo Eye Hospital Bandung from 2013 to 2015 - Yee She Hui; Raden Angga Kartiwa; Resti Gradia Dwiwina (Althea Medical Journal, 2017)
Background: Basal cell carcinoma (BCC) has been proved to have the highest incidence among eyelid malignancies. Basal cell carcinoma is the most common invasive cancer in humans. It is capable of causing extensive tissue destruction. The aim of the study was to identify the characteristics of adult patients with malignant eyelid BCC in Cicendo Eye Hospital Bandung.